Increased striatal functional connectivity with auditory cortex in tinnitus - Hinkley, Leighton B.; Mizuiri, Danielle; Hong, OiSaeng; Nagarajan, Srikantan S.; Cheung, Steven W. (Frontiers in Human Neuroscience, 2015)
Tinnitus is a common auditory perceptual disorder whose neural substrates are under intense debate. One physiologically based model posits the dorsal striatum to play a key role in gating auditory phantoms to perceptual awareness. Here, we directly test this model along with the roles of auditory and auditory-limbic networks in tinnitus noninvasively by comparing resting-state fMRI functional connectivity patterns in chronic tinnitus patients against matched control subjects without hearing loss. We assess resting-state functional connectivity of the caudate dorsal striatum (area LC), caudate head (CH), nucleus accumbens (NA), and primary auditory cortex (A1) to determine patterns of abnormal connectivity. In chronic tinnitus, increases in ipsilateral striatal-auditory cortical connectivity are found consistently only in area LC. Other patterns of increased connectivity are as follows: 1) right striatal area LC, A1, caudate head and NA with parietal cortex, 2) left and right caudate heads with dorsal pre-frontal cortex, 3) NA and A1 with cerebellum, hippocampus, visual and ventral pre-frontal cortex. Those findings provide further support for a striatal gating model of tinnitus, where dysfunctionally permissive area LC enables auditory phantoms to reach perceptual awareness.